MASKULINITAS DALAM NASKAH DRAMA AYAHKU PULANG KARYA USMAR ISMAIL DAN PEMANFAATANNYA SEBAGAI MATERI AJAR DRAMA DI SMK - Muh. Reva Fitra Rahmawan; Budhi Setiawan (Universitas Batanghari, 2025)
This study aims to (1) describe the forms of masculinity in the drama script Ayahku Pulang by Usmar Ismail, and (2) explain its utilization as teaching material in literature learning at Vocational High Schools (SMK). This research is a descriptive qualitative study. The data sources include the drama script Ayahku Pulang, Indonesian language teachers, and students. The sampling technique used is purposive sampling. Data were collected through document analysis and in-depth interviews. To test the validity of the data, triangulation was applied. The data were analyzed using an interactive analysis model. This research adopts Janet Saltzman Chafetz’s theory of masculinity as the analytical framework. The findings show that the drama script Ayahku Pulang contains seven aspects of masculinity as outlined by Chafetz, namely physical, functional, sexual, emotional, intellectual, interpersonal, and other personal traits. Each of these aspects is strongly represented through the main characters, especially Raden Saleh and Gunarto, who portray various social and psychological dynamics of being male within a family context. Furthermore, the interview results indicate that the script has great potential to be used as teaching material in SMK, as it is relevant to the students’ daily lives and includes gender awareness that supports the holistic development of students' character. Therefore, the use of the Ayahku Pulang script in literature learning is expected not only to strengthen students’ literary literacy skills but also to foster empathy, social understanding, and critical thinking about gender equality issues in society